Socioeconomic status and internet addiction: double-mediated moderation - Wei Chen; Yujing Gao; Rongrong Ren; Yajie Bi; Yaxi Liao (BMC Public Health)
Abstract Background Internet addiction is typically linked with a variety of psychological and behavioral problems, the prevalence of Internet addiction among Chinese college students was higher than that of the general population. Objective The present study aimed to test the mediating and moderating effects of socioeconomic status (SES), loneliness, alienation and grade on Internet addiction among Chinese college students. Methods Total of 496 college students were studied, partial least square structural equation modeling (PLS-SEM) was conducted to analyze the obtained data. Results The study found that SES can negatively predict Internet addiction (β=-0.145, p < 0.001). Moreover, loneliness and alienation play separate (β=-0.098, p < 0.001; β=-0.046, p < 0.01) and serial (β=-0.071, p < 0.001) mediating roles between SES and Internet addiction, and multigroup analysis showed that grade (sophomore year as the baseline) plays a moderation role in the association between SES → Internet addiction (sophomores vs. juniors; β = 0.249, p < 0.05) and SES →loneliness (sophomore vs. seniors; β = 0.255, p < 0.05). The VAF value was 70.27% for the mediation effect of the loneliness and alienation in the relationship between SES and Internet addiction. Conclusions SES not only has a direct effect on college students’ Internet addiction behavior but also has an indirect effect on it through the chain mediation effect of loneliness and alienation. The study reveals that grade level moderates the effects, suggesting tailored interventions are needed. This research could inform measures to mitigate addiction by addressing SES, loneliness, and alienation.